Employment and Wages in the Public Sector : A Cross-Country Study. (IMF Working Papers; Working Paper ;, 1995)
We study the determinants of employment and wages in the public sector, using a new set of panel data for 34 LDCs and 21 OECD countries from 1972-992, by estimating equations suggested by an efficiency wage model. We find that government employment is positively associated with the relaxation of resource constraints (the revenue-to-GDP ratio and foreign financing in the case of developing countries and GDP per capita in the case of OECD countries), urbanization, the level of education, and certain countercyclical pressures for government hiring (the real effective exchange rate for developing countries and private employment for OECD countries). Certain measures of government wages are positively associated with government revenues and negatively associated with the level of education, government debt, and countercyclical pressures.